KEBIJAKAN FISKAL DALAM MENGATASI KETIMPANGAN PENDAPATAN DI INDONESIA - Yuliani, Novi Mela; Paturochman, Iwan Ridwan; Mubarok, Agus Triana; Muzaki, Rizki Ali (Jurnal Bina Bangsa Ekonomika, 2025)
This study aims to determine the influence of fiscal policy on income inequality in Indonesia in 2011-2022. The object of research used in this study is Indonesia, while the variables used are income inequality as a dependent variable and fiscal policy with social assistance spending instruments and education spending from the expenditure side, as well as regional taxes from the revenue side which move as independent variables. The type of research used is quantitative research with the multiple linear regression analysis method or OLS (Ordinary Least Square) using E-Views 12 software. The data used in this study is secondary data obtained from the World Bank and the Directorate General of Fiscal Balance (DJPK) of the Ministry of Finance with a time series data type in the 2011-2022 period. The results of this study show that social assistance expenditure and regional taxes have a negative and significant relationship both partially and simultaneously with income inequality in Indonesia. However, education spending has a positive and insignificant effect on income inequality